A case study on Towyongi Sdn Bhd feasibility study on export pottery to Spain - Chen, Shiang Yih (2001)
Towyongi Sdn. Bhd. is a medium size private limited company involved in pottery design and manufacture. In order to protect the interest of shareholders and strive to provide attractive return to share holder fund, where it had made drastic decision to move from the backyard manufacture to the Ceramic Park in year 1993 and bought a set of new kiln machinery from Italy. Towyongi needed to expand the market reach by exporting their products to oversea by themselves. Small domestic market size is one of the major problems for Towyongi Sdn. Bhd. production as well as for most other industrial production in Malaysia. In addition to the smallness of the total market size, the diversified demand of consumers form top-quality products to low-end products makes the production unit of each product volume even smaller. This limited market size is largely preventing the autonomous growth of Towyongi Sdn. Bhd. in Malaysia. Towyongi Sdn. Bhd. has no experience of know-how of export. Even the products had been exported; it is also due to the trading house available, not by them.